D.I. Pisarev on monism, materialism and partisanship of philosophy - Andrey A. Chernykh (Семиотические исследования)
An episode from the discussion of N.G. Chernyshevsky’s article The Anthropological Principle in Philosophy is considered. It is shown how D.I. Pisarev defended the materialistic worldview against his opponents’ criticism. The study sets out the following tasks: 1) to identify the relevant ontognoseological ideas of D.I. Pisarev for contemporary ontology and theories of cognition; 2) to examine the principle of partisanship in philosophy using examples from Pisarev’s works. The aim of the study is to clarify the specific features of Pisarev’s philosophical views and to justify his relevance as a thinker. The methodology is based on the principle of partisanship, i.e. the classification of philosophical systems within the paradigms of idealism–materialism and dualism–monism, according to which the philosopher’s ontognoseological views serve as the foundation for his political, anthropological, ethical, aesthetic, and other ideas. The primary sources analyzed are texts by D.I. Pisarev in which he defended Chernyshevsky’s position in the discussion of the anthropological principle. Texts by other thinkers with whom Pisarev engaged in polemics, such as P.L. Lavrov, P.D. Yurkevich, and others, are also taken into account. The study’s novelty lies in showing that the principle of partisanship in philosophy does not vulgarize the understanding of ontological and gnoseological problems, but rather helps reveal the nature of ontognoseological questions. The study also highlights the anthropological turn in Russian philosophy in the 19th century. The conclusion emphasizes the high significance of D.I. Pisarev for both Russian and global philosophical thought, particularly in the fields of ontology and gnoseology